Morphological and biological characteristics of black-headed caterpillar, Opisina arenosella (Lepidoptera: Xyloryctidae) - HONG-UNG NGUYEN; THI-THANH-NGA SON; THI-XUAN TRINH; NGUYEN-QUOC-KHANH CHAU (Society for Indonesian Biodiversity, 2025)
Abstract. Nguyen H-U, Son T-T-N, Trinh T-X, Chau N-Q-K. 2025. Morphological and biological characteristics of black-headed caterpillar, Opisina arenosella (Lepidoptera: Xyloryctidae). Biodiversitas 26: 3021-3029. The black-headed caterpillar, Opisina arenosella, has recently emerged as a significant pest affecting coconut production in the Mekong Delta, Vietnam. Research on the morphological and biological characteristics of this species was conducted at the laboratory of Tra Vinh University, Vietnam, to serve as a basis for the development of its effective management strategies. The results revealed that O. arenosella eggs were oval, creamy yellow in color, turning reddish brown just before hatching. The average size of the eggs was 0.72±0.13 mm x 0.42±0.10 mm. The larval color was remarkably diverse, varying from white to reddish-brown with multiple stripes on the body. They have a black or dark brown head and range in length from 1.35±0.12 mm to 15.10±2.97 mm, with widths from 0.2±0.02 mm to 1.65±0.07 mm. Opisina arenosella pupae were initially grayish-white and later transform into blackish-brown. The average size was 11.33±1.25 mm x 2.63±0.38 mm for female pupae and 9.30±0.99 mm x 2.07±0.30 mm for male pupae. Female adults had an average body length of 10.7±1.47 mm, light gray, while male adults were darker, averaging 8.62±0.72 mm in body length. The average life cycle of O. arenosella was 75.6±26.9 days, which includes 5.62±1.70 days for the egg stage, 38.7±1.89 days for larval stage, amd 8.02±1.18 days for male pupae and 8.05±0.85 days for female pupae.